Boosting Photocatalytic Activity Using Vanadium Doped Titanium Oxide with Reduced Graphene Oxide (RGO)/Semiconductor Nanocomposites - Zahra, Kiran; Habib, Muhammad Salman; Athar, Muhammad (Journal of Sustainable Materials Processing and Management, 2023)
Textile waste materials are increasing day by day with the depletion of water and increasing the concentration of ions present in the water that produce toxicity. The sustainability of the materials to rule out this toxicity can be done by Reduced Graphene Oxide synthesized by modified Hummer’s method. The composite of V-doped TiO2 and RGO was synthesized by hydrothermal method and V-doped TiO2/RGO and perfluorocarbon synthesized by sonication. The product was characterized by the powder X-ray Diffraction method. It has confirmed the synthesis of the product. Ultraviolet/visible spectroscopy was employed to study the photocatalytic activity of the product for the degradation of methylene blue which is an organic dye and hazardous to the environment.